Ionothermal Synthesis of Metal Oxide-Based Nanocatalysts and Their Application towards the Oxidative Desulfurization of Dibenzothiophene - Bader Alenazi; Ali Alsalme; Saad G. Alshammari; Rais Ahmad Khan; Mohammed Rafiq H. Siddiqui (Journal of Chemistry)
Herein, different types of metal-containing ionic liquid (IL) complexes and various metal oxide-based nanocatalysts have been successfully prepared (from ionic liquids) and applied for the oxidative desulfurization (ODS) of dibenzothiophene (DBT). The ILs complexes are comprised of N,N′-dialkylimidazolium salts of the type [RMIM-Cl]2[MCln], where [RMIM+] = 1 alkyl-3-methylimidazolium and M = Mn(II)/Fe(II)/Ni(II)/Co(II). These complexes were prepared using an easy synthetic route by refluxing the methanolic solutions of imidazolium chloride and metal chlorides under facile conditions. The as-prepared complexes were further used as precursors during the ionothermal and chemical synthesis of various metal oxide-based nanocatalysts. The resulting ILs salts and metal oxides NPs have been characterized by FT-IR, TGA, XRD, SEM, and TEM analysis. The results indicate that thermal and chemical treatment of ILs based precursor has produced different phases of metal oxide NPs. The calcination produced α-Fe2O3, Mn3O4, and Co3O4, NPs, whereas the chemical treatment of the ILs salts have led to the production of Fe3O4, Mn2O3, and α-Co(OH)2. All the as-prepared salts and metal oxide-based nanocatalysts were used as catalysts towards ODS of dibenzothiophene. The oxidation of dibenzothiophene was performed at atmospheric conditions using hydrogen peroxide as the oxygen donor. Among various catalysts, the thermally obtained metal oxide NPs such as α-Fe2O3, Mn3O4, and Co3O4, have demonstrated relatively superior catalytic activities compared to the other materials. For example, among these nanocatalysts, α-Fe2O3 has exhibited a maximum conversion (∼99%) of dibenzothiophene (DBT) to dibenzothiophene sulfone (DBTO2).